Podoba Slovencev v Bartschevem romanu Das deutsche Leid - Čeh Steger, Jožica (Slavistična revija, 2017)
Cultural studies have shown that verbal depictions of non-Germanic nations in the AustroHungarian Empire in the dominant German discourse demand more investigative research which would expose the myth of a multicultural and supranational Austria-Hungary. German cultural colonialism has constructed negative, even hostile images of the foreign/the other. This article examines Bartsch's German nationalist novel Das Deutsche Lied and its depictions of Slovenes as foreign/other, as well as asymmetric German-Slovene biculturalism in Lower Styria in the period of ethnic friction and the unrelenting Germanization prior to World War I.
Keywords: "Das deutsche Leid"; avstrijski roman; Bartsch, Rudolf Hans; drugi; germanizacija; podobe tujega; Slovenci; Slovenes; Spodnja Štajerska; Styria; večkulturnost